2019
DOI: 10.1021/acs.molpharmaceut.8b01297
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Machine Learning Comparisons of HIV Cell-based and Reverse Transcriptase Data Sets

Abstract: The human immunodeficiency virus (HIV) causes over a million deaths every year and has a huge economic impact in many countries. The first class of drugs approved were nucleoside reverse transcriptase inhibitors. A newer generation of reverse transcriptase inhibitors have become susceptible to drug resistant strains of HIV, and hence, alternatives are urgently needed. We have recently pioneered the use of Bayesian machine learning to generate models with public data to identify new compounds for testing agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(114 citation statements)
references
References 81 publications
4
109
0
1
Order By: Relevance
“…Machine learning models for chordoma drug discovery. Several recently published studies of compounds screened against chordoma cell lines 20,21 were used to generate Bayesian machine learning models with our Assay Central software 10,12,[22][23][24][25][26][27][28][29] . In one published chordoma study 1097 compounds were screened against 3 chordoma cell lines (U-CH1, U-CH2, MUG-Chor1) and 27 had chordoma selective cytotoxicity 20 and many of these were EGFR inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Machine learning models for chordoma drug discovery. Several recently published studies of compounds screened against chordoma cell lines 20,21 were used to generate Bayesian machine learning models with our Assay Central software 10,12,[22][23][24][25][26][27][28][29] . In one published chordoma study 1097 compounds were screened against 3 chordoma cell lines (U-CH1, U-CH2, MUG-Chor1) and 27 had chordoma selective cytotoxicity 20 and many of these were EGFR inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously described Assay Central TM which uses a Bayesian method, and compared it with other methods against a relatively small number of targets such as drug induced liver injury 50 , estrogen receptor 51 , M. tuberculosis 52 , non-nucleoside reverse transcriptase and whole cell HIV 53 . In general, we found that DNN generally performed the best for five-fold cross validation, but with external test sets this superiority was not observed and generally Assay Central TM performed comparably with SVM classification or DNN.…”
Section: Discussionmentioning
confidence: 99%
“…we have used several of these auto-curated models to predict data that was previously curated and used for training or testing models for HIV whole cell, HIV reverse transcriptase and Mtb inhibition 52,53 . In all cases the ROC for these test sets was > 0.7 ( Figure S4 and S5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations